A Prospective Study on the Effectiveness of Arsenic Trioxide (ATO) in Remission Induction of Acute Promyelocytic Leukemia (APL) - Anis, Mohammad Abdullah Al; Khan, Mohiuddin Ahmed; Afrosa, Salma; Islam, M Sirajul; Biswas, Akhil Ranjan; Ara, Tasnim; Ali, Muhammad; Islam, Manirul; Naznin, Humayra; Akhter, Mafruha; et al. (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Background: Arsenic Trioxide (ATO) as a single agent, has proven efficacy in inducing molecular remission in patients with Acute Promyelocytic Leukemia (APL). It is commonly used to treat relapsed APL. But there is Limited study on ATO in the management of newly diagnosed cases of APL. The concerned study was done to evaluate the effectiveness and outcome of ATO in remission induction of new cases of APL in the context of a limited resource hospital in Bangladesh. Methods: From March 2008 to March 2010, 20 patients with Promyelocytic Leukemia (PML) / Retinoic Acid Receptor ? (RAR ?) + newly diagnosed APL were enrolled. All patients were treated with a regimen of single-agent arsenic trioxide till remission at our center. After remission the regimen was administered on outpatient basis. Results: Overall 15 (75%) patients achieved complete hematological remission. 12 (80%) patients achieved molecular remission after induction phase and 3 (20%) after completion of consolidation phase. At a median follow up of 36 months (Range 25 -44 months), Disease Free Survival (DFS) and Overall Survival (OS) 86.6% and 85.3% respectively. Relatively young patients with long form of t (15;17) had shown good response with this response. However, the response is slower than All Trans Retinoic Acid (ATRA). Patients presenting with high White Blood Cell (WBC) count, low platelet count, variable form of t (15;17) are found to respond poorly. The toxicity profile, in the majority, was mild and reversible. Treatment cost was also reduced than that of conventional regimen. Conclusion: Single-agent arsenic trioxide as used in this study in the management of newly diagnosed cases of APL is safe, cost beneficent and is associated with durable responses. But additional interventions as combining ATRA with ATO would probably required in high risk cases. Chatt Maa Shi Hosp Med Coll J; Vol.14 (2); Jul 2015; Page 5-10